Women Empowerment Through Girls Go Beyond Training In Teknokrat University - Shana Makhmood Khan; Hj Tien Yulianti (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2024)
Teknokrat University established the 'Girls Go Beyond' training program in response to the obstacles that many teen girls in Indonesia experience, notably in terms of access to education and opportunity. This program seeks to empower young women by providing them with the necessary skills, tools, and knowledge to successfully navigate their futures. The purpose is to make teenage girls develop a grasp of their innate skills and legal rights, allowing them to make educated life decisions. The program uses a variety of educational technologies, including WhatsApp, Google Classroom, and Google Forms, to deliver information and create interactive learning experiences. Through this campaign, teen girls aged 17-19 from the university's first semester cohort can learn about their rights, make informed decisions, and express themselves freely. This abstract summarizes the training program's aims and the participation of 39 female students, emphasizing the necessity of encouraging young women to reach their full potential.